An Efficient Visible and Near‐Infrared (NIR) Emitting SmIII Metal–Organic Framework (Sm‐MOF) Sensitized by Excited‐State Intramolecular Proton Transfer (ESIPT) Ligand. Issue 12 (25th May 2016) - Chen, Ling; Zhang, Hao; Pan, Mei; Wei, Zhang‐Wen; Wang, Hai‐Ping; Fan, Ya‐Nan; Su, Cheng‐Yong
Abstract: We report herein an unprecedented example of a luminescent Sm III metal–organic framework (Sm‐MOF), in which both the visible and near‐infrared (NIR) emissions of Sm 3+ ions are able to be sensitized by an excited‐state intramolecular proton transfer (ESIPT) ligand. Due to the solvent‐mediated interchange between enol and keto excited states of the ligand and subsequent energy transfer rate to Sm 3+ ions, the luminescent decay lifetime of the Sm‐MOF can be tuned in different solvent‐grinding systems. Abstract : Energy transfer between two states ! Sm III ‐MOF was synthesized from an excited‐state intramolecular proton transfer (ESIPT) ligand to have highly sensitized and solvent‐responsive luminescence in both visible and near‐infrared (NIR) regions (see figure).